Resources, environment and engineering proceedings of the 2014 Technical Congress on Resources, Environment and Engineering (CREE 2014), Hong Kong, 6-7 September 2014 - Xie, Liquan (CRC Press, Taylor & Francis Group, 2015)
Resources, Environment and Engineering contains 66 technical papers from the 2014 Technical Congress on Resources, Environment and Engineering (CREE 2014, Hong Kong, 6-7 September 2014, including the 4th Technical Conference on Chemical Engineering, CCE 2014). The contributions review recent technological advances in the fields of resources and the environment, and showcase the developments occurring in the areas of resources, environmental protection and associated engineering practice.